Students’ grammatical error analysis in the recount text translation - Nilam Puspita Sari; Gede Eka Putrawan; Rafista Deviyanti (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This research aims to determine the types of grammatical errors that students make the most and least frequently, as well as the causes of those errors, using the Surface Strategy Taxonomy that was identified in students' recount text translation. The participants in this study were SMAN 1 Pringsewu first-graders in the academic year 2020/2021. This research adopted a descriptive qualitative method by using a translation task and questionnaire for the instruments. According to the Surface Strategy Taxonomy, the students made all types of errors: omission, addition, misformation, and misordering. In recount text translation based on Surface Strategy Taxonomy, the most common error made by students was misformation, whereas the least frequent error type was misordering. Problems with the target language, mother-tongue interference, a lack of eagerness to learn the target language, a lack of confidence, and the absence of error feedback from the teacher were all possible causes of those errors. This indicates that the students’ English grammar understanding was still limited. Therefore, the English teacher is expected to solve it by providing appropriate teaching methods and materials to reduce errors.